Tiliha A. Y. Translation of toponyms as components of fantasy fiction world view representation in English-Ukrainian - Tiliha A. Y. (Philological Treatises, 2020)
The present article deals with the translation of toponyms in texts of fantasy genre on the basis of fantasy fiction world view representation as a combination of semantic, morphologic and etymologic analysis.